The Implementation of PBL Assisted by Truth or Dare Media to Improve Students' PKN Understanding - Nur Ariska Syam; Firdha Razak; A. Shyam Sarjani Alam (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2026)
This study aimed to improve fifth-grade students' conceptual understanding in Civics Education through the implementation of the Problem-Based Learning (PBL) model assisted by Truth or Dare card media at SDN 2 Labakkang. This classroom action research was conducted in two cycles involving 33 students. Each cycle consisted of planning, action, observation, and reflection. Data were collected through observation, concept-understanding tests, and documentation, then analyzed using descriptive quantitative and qualitative techniques. The results showed that students' conceptual understanding improved from a low category in cycle I to a high category in cycle II. The mean score increased from 46.12 in cycle I to 77.24 in cycle II, while learning mastery increased from 21.21% to 87.87%. Student activity and teacher activity also improved across cycles. These findings indicate that integrating PBL with Truth or Dare card media can create interactive, contextual, and enjoyable learning experiences that support students' understanding of Civics concepts.